Timing of Recovery After Surgery for Patients With Degenerative Cervical Myelopathy: An Observational Study From the Canadian Spine Outcomes and Research Network. Issue 2 (15th November 2022) - Evaniew, Nathan; Coyle, Matthew; Rampersaud, Y. Raja; Bailey, Christopher S.; Jacobs, W. Bradley; Cadotte, David W.; Thomas, Kenneth C.; Attabib, Najmedden; Paquet, Jérôme; Nataraj, Andrew; Christie, Sean D.; Weber, Michael H.; et al.
Abstract : BACKGROUND: The time course over which postoperative neurological recovery occurs after surgery for degenerative cervical myelopathy occurs is poorly understood. OBJECTIVE: To determine the time point at which patients experience significant neurological improvement. METHODS: We reviewed data from an ongoing prospective multicenter cohort study. We measured neurological function at 3 months, 1 year, and 2 years after surgery using the modified Japanese Orthopedic Association (mJOA) scale. We implemented minimal clinical important differences (MCIDs) to guide interpretation of mJOA scores, and we used 1-way analysis of variance to compare changes between follow-up intervals. RESULTS: Among 330 patients, the mean overall mJOA improved from 12.9 (SD 2.6) to 14.6 (SD 2.4) at 3 months, 14.7 (SD 2.4) at 1 year, and 14.8 (SD 2.5) at 2 years. The difference in means was statistically significant ( P < .01) at the interval from baseline to 3 months postoperatively, but not from 3 months to 1 year or 1 year to 2 years. The MCID was reached by 161 patients at 3 months, 32 more at 1 year, and 15 more at 2 years, with a statistically significant difference only at 3 months. Patients with moderate or severe disease reached the MCID more frequently than those with mild disease. CONCLUSION: Among patients who underwent surgery for degenerative cervical myelopathy, most significant neurological improvement occurred by 3 months after surgery. These findings will facilitate valid discussions about postoperative expectations during shared clinical decision making between patients and their surgeons. Abstract :